Non-synonymous variant (Gly307Ser) in CD226 is associated with susceptibility to multiple autoimmune diseases (2010)
Objectives. Recently, a non-synonymous (Gly307Ser) variant, rs763361, in the CD226 gene was shown to be associated with multiple autoimmune diseases (ADs) in European Caucasian populations. However, shared autoimmunity with CD226 has not been evaluated in non-European populations. The aim of the present study is to assess the association of this single nucleotide polymorphism (SNP) with ADs in non-European populations. Methods. To replicate this association in non-European populations, we evaluated case-control association between rs763361 and coeliac disease (CED) samples from Argentina; SLE, RA, type-1 diabetes (T1D) and primary SS (pSS) from Colombia; and SLE samples from China and Japan. We genotyped rs763361 and evaluated its genetic association with multiple ADs, using ?2-test. For each association, odds ratio (OR) and 95% CI were calculated. Results. We show that rs763361 is significantly associated with Argentinean CED (P = 0.0009, OR= 1.60). We also observed a trend of possible association with Chinese SLE (P = 0.01, OR= 1.19), RA (P = 0.047, OR= 1.25), SLE (P = 0.0899, OR= 1.24) and pSS (P = 0.09, OR= 1.33) in Colombians. Meta-analyses for SLE (using our three populations) and T1D (our population and three published populations) yielded significant association with rs763361, P = 0.009 (OR = 1.16) and P = 1.1.46×10-9 (OR = 1.14), respectively. Conclusions. Our results demonstrate that the coding variant rs763361 in CD226 gene is associated with multiple ADs in non-European populations. © The Author 2010. Published by Oxford University Press on behalf of the British Society for Rheumatology. All rights reserved. For Permissions, please email: journals.permissions@oxfordjournals.org.